2001
DOI: 10.1590/s0100-204x2001001100002
|View full text |Cite
|
Sign up to set email alerts
|

Resposta do cafeeiro à adubação potássica em safras de baixa e alta produção

Abstract: Foram realizados dois experimentos em lavouras cafeeiras das Fazendas Experimentais da Epamig, em Minas Gerais, com o objetivo de estudar a resposta do cafeeiro à adubação potássica (fontes e doses) nas safras de baixa e alta produção em dois Latossolos. Os experimentos foram instalados em lavouras de café da cultivar Catuaí Vermelho, linhagem MG-99, plantadas seis anos antes, no espaçamento de 3,5 x 0,7 m. O delineamento experimental foi em blocos casualizados, com quatro repetições, no esquema de parcelas su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
(9 reference statements)
1
9
0
3
Order By: Relevance
“…According to Matiello et al (2010), N and K are the most required nutrients by coffee trees, but N is the most required in the low-yielding growing season (leaf growth) and K is the most required in the high-yielding growing season (fruit and grain filling). The results are consistent with those of Silva et al (2001), who demonstrated that this behavior is due to greater nutrient uptake and thus, a higher nutrient export in the high-yielding growing season.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…According to Matiello et al (2010), N and K are the most required nutrients by coffee trees, but N is the most required in the low-yielding growing season (leaf growth) and K is the most required in the high-yielding growing season (fruit and grain filling). The results are consistent with those of Silva et al (2001), who demonstrated that this behavior is due to greater nutrient uptake and thus, a higher nutrient export in the high-yielding growing season.…”
Section: Resultssupporting
confidence: 91%
“…According to Alvarez V. et al (1999), the probability of coffee response to K fertilization is high, if soil K concentration ranges from 1.0 to 1.75 mmol c dm -3 . Nevertheless, Silva et al (2001) observed K fertilization effects on coffee when soil K concentration in a Red Latosol was 1.8 mmol c dm -3 and the highest yields were harvested at a mean available soil K of 6.4 and 4.0 mmol c dm -3 K (Mehlich-1) in low and high-yielding growing seasons, respectively.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations